SCHEMATIC STRUCTURE AND METADISCOURSE ANALYSIS OF BEAUTY PAGEANT-WINNING ANSWERS - Khan, Shana Makhmood; Suprayogi, Suprayogi (JOURNAL OF LANGUAGE, 2024)
This research delves into the schematic structure and metadiscourse markers utilized in the winning responses of prominent Beauty Pageants. Through qualitative investigation, it explores how candidates strategically organize their answers and employ language to effectively convey their perspectives. Drawing upon theoretical frameworks from schematic structure theory and metadiscourse classification, the study analyzes transcripts of final question and answer segments from Beauty Pageant events spanning from 2015 to 2023. Utilizing 36 transcribed texts sourced from YouTube archives and transcription, the study sheds light on the nuanced structure of responses, highlighting patterns in linguistic expression. Despite the extensive data from Beauty Pageants, differences in format and accessibility across events were observed. This study contributes to understanding the intricacies of communication within beauty pageants, elucidating the structural elements of successful responses. Ultimately, it advances our comprehension of pageant competitions on both large and small scales. Furthermore, this research provides valuable insights for individuals interested in participating in beauty pageants, offering guidance on the effective use of metadiscourse markers for practice and application.